Matching of trucks to loaders for the haulage system at billiton Bogosu Gold Limited - Awotwe, Kofi Emmanuel (2012)
Project report submitted in partial fulfilment of the requirements for the Postgraduate (Professional) Diploma Degree in Mining Engineering.